Customary Regulations for Awig-Awig as A Depending the State-Based Environmental Conservation Effort in the Village of Pakraman, Bai Province - W. Yulianingsih; P. Hastuti (Nusantara Science and Technology Proceedings)
The existence of customary law systems in various regions in Indonesia continues to be explored. the reason is that in some contexts the legal and social issues, customary law is a more effective trigger than national law. The community life in Bali which is known in the container of pakraman village has long existed because of its attachment to customary law. The attachment is based on values and habits that have grown among all citizens to respect each other, including in terms of environmental conservation, which is regulated in the form of custom regulations called awig-awig. This study aims to analyze: (i) the background of the existence of awig-awig customary regulations in the pakraman village, Bali Province, (ii) the establishment of awig-awig as an effort to preserve the environment, (iii) proof of the defense of the state in the implementation of awig-awig. This study uses an empirical juridical approach and then analyzed descriptively qualitative. The results show that pakraman village is a customary law community in the province of Bali which has village autonomy one of which sets its own rules in the form of awig-awig. This authority is formally juridically regulated in the regional regulations of the Province of Bali and recognized in the constitution. Awig-awig is a rule made by pakraman village manners that are used as a guide in the implementation of Tri Hita Kirana. In this case, the noble values that apply in the life of the Pakraman village community through awig-awig to protect and manage the environment in a sustainable manner. Awig-awig is not only based on the teachings of Hindu Tri Hita Kirana but also based on Pancasila to achieve the goals of the country. This is a reflection of the spirit of defending the country in the implementation of awig-awig.